Assessing health care students' intentions and motivations for learning: the Healthcare Learning and Studying Inventory (HLSI). - Baxter, L; Mattick, K; Kuyken, W (2013)
Inventories that measure approaches to learning have revealed that certain approaches are associated with better academic performance. However, these inventories were developed primarily with higher education students on non-vocational courses and recent research shows they fail to capture the full range of healthcare students' intentions and motivations for learning. To develop a new inventory measuring approaches to learning that addresses these shortfalls and is relevant to students on vocational courses in healthcare. In depth interviews with healthcare students were performed to understand the full range of healthcare students' intentions and motivations. The data were used to create a draft inventory, which was reviewed by interview participants and then tested with medical students. The final inventory was piloted with 303 healthcare students across six disciplines. Exploratory factor analysis was used to identify groups of related items within the inventory. The research produced a 32 item scale based on rich qualitative data, with a four factor structure and good internal consistency. A desire to link theory and practice was a distinctive feature of healthcare students. The new inventory contains nuanced items that enable a better understanding of their common and distinctive intentions and motivations. This study suggests that healthcare student populations have some unique intentions and motivations for learning and therefore require a bespoke inventory to ensure that important aspects are not missed. It offers a new tool for meaningful future research, the Healthcare Learning and Studying Inventory (HLSI).